2014
DOI: 10.1016/j.virusres.2014.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Porcine epidemic diarrhea virus infects and replicates in porcine alveolar macrophages

Abstract: Porcine epidemic diarrhea virus (PEDV) is a causative agent of porcine epidemic diarrhea; consequently, the small intestine was believed to be its only target organ. In this study, we found that PEDV infected not only the small intestines, but also the respiratory tract. Infection and replication of PEDV in the respiratory tract from naturally PEDV-infected piglets were examined by reverse transcription polymerase chain reaction, immunohistochemistry, and virus re-isolation. Our observations were confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Here, we have developed a platform to facilitate the in vitro culture of PEDV by engineering Vero E6 cells to permanently express pAPN as a substrate for PEDV propagation. This modified cell line can augment PEDV replication, based on the observation that the majority of PEDV-positive intestinal samples used in our study gave rise to progressive syncytium formation in VeroE6-APN but not in parental VeroE6 cells (data not shown Recovery of PEDV using a full-length infectious clone been shown that growth of PEDV in these cells is markedly slower than in Vero cells (Cong et al, 2015;Park & Shin, 2014). Moreover, whilst ST cells permanently expressing high levels of pAPN (ST-pAPN-H/Q cells) could be efficiently infected by PEDV, the plaque size of PEDV-infected ST-pAPN-H/Q cells is apparently smaller than that of infected Vero cells (Nam & Lee, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have developed a platform to facilitate the in vitro culture of PEDV by engineering Vero E6 cells to permanently express pAPN as a substrate for PEDV propagation. This modified cell line can augment PEDV replication, based on the observation that the majority of PEDV-positive intestinal samples used in our study gave rise to progressive syncytium formation in VeroE6-APN but not in parental VeroE6 cells (data not shown Recovery of PEDV using a full-length infectious clone been shown that growth of PEDV in these cells is markedly slower than in Vero cells (Cong et al, 2015;Park & Shin, 2014). Moreover, whilst ST cells permanently expressing high levels of pAPN (ST-pAPN-H/Q cells) could be efficiently infected by PEDV, the plaque size of PEDV-infected ST-pAPN-H/Q cells is apparently smaller than that of infected Vero cells (Nam & Lee, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, PEDV antigens were not detected by immunostaining within the spleen, liver or lungs of CV777‐infected pigs (Debouck et al., ) or in lungs of PEDV PC21A‐infected pigs (Jung et al., ), but the sensitivity of the RT‐qPCR assays used here is likely higher than the sensitivity of the immunostaining procedures. It has been reported (Park and Shin, ) that PEDV can replicate in pulmonary macrophages in vivo and thus extra‐intestinal replication of PEDV seems possible (Jung and Saif, ). The results presented here indicate that the US PEDV produced slightly more severe clinical signs than the cell culture‐grown Br1/87 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Although macrophages infiltrated in the lamina propria also contained viral antigen as revealed by immunohistochemistry staining (Lee et al, 2000), it remains to be determined whether PEDV actually productively infected the intestinal macrophages. Porcine alveolar macrophages have been shown to support PEDV replication (Park and Shin, 2014). One recent study suggests that PEDV only replicates in Mo-DC prior to 24 h after infection, but not at later time points, as determined by virus titration of culture supernatants (Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%